The analysis of the degree of flood risk in the middle Bobr valley = Analiza stopnia zagrożenia powodziowego w dolinie środkowego Bobru - Hudak, Magda; Kołodziejczyk, Urszula; Kostecki, Jakub; Nowogoński, Ireneusz; Żebrowska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the impact of rainfall on the degree of flood risk in the basin of the middle Bobr River in western Poland. When the average rainfall level reaches 15 to 20 mm, this apparently calm river may dramatically change its character within just one week.
Keywords: flood risk; valley of the Bobr River; flood in Poland; zagrożenie powodziowe; dolina rzeki Bóbr